Composing Heterophony: Arranging and Adapting Global Musics for Intercultural Ensembles - Silpayamanant, Jon (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2021)
The usage of heterophony has changed significantly since it was coined by Guido Adler in 1908 to signify an other in opposition to Western polyphony. It was first used to demonstrate an evolutionary progression from a more primitive form of music making to a purportedly more developed polyphony that had supposedly only been achieved in the West. Starting from the idea of a continuum between monophony and polyphony, with heterophony falling somewhere in the middle, this article contends that it is more useful to conceive of all three as coexisting and reflecting expressions of different functions of music. A more fluid concept of all three descriptive terms is far more useful as an analytic tool and can help to reveal a wide variety of hybridization and collaborative interaction between musicians with diverse musical backgrounds.